2014
DOI: 10.1080/07373937.2013.879387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Germination Process and Drying Temperature on Gamma-Aminobutyric Acid (GABA) and Starch Digestibility of Germinated Brown Rice

Abstract: In this work, germination method, germination time, and drying temperature were investigated for their effects on gammaaminobutyric acid (GABA) and starch digestibility. The germination method and germination time influenced the GABA and dietary fiber contents as well as starch and glucose, but both factors did not provide a faster hydrolysis of starch for germinated brown rice because of the dietary fiber. When the germinated samples were dried by a hot-air fluidized bed dryer at 130 or 150 C, the GABA conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Inconsistent results in terms of parboiling effects on GABA content of germinated rice have been reported. Chungcharoen et al (2014), Komatsuzaki et al (2007), and Srisang et al (2010Srisang et al ( , 2011 reported that germinated rice had unchanged or significantly increased GABA content after steaming and drying; however, Noomhorm (2011, 2015) reported up to 50% reduction in GABA after parboiling with drying.…”
Section: Resultsmentioning
confidence: 99%
“…Inconsistent results in terms of parboiling effects on GABA content of germinated rice have been reported. Chungcharoen et al (2014), Komatsuzaki et al (2007), and Srisang et al (2010Srisang et al ( , 2011 reported that germinated rice had unchanged or significantly increased GABA content after steaming and drying; however, Noomhorm (2011, 2015) reported up to 50% reduction in GABA after parboiling with drying.…”
Section: Resultsmentioning
confidence: 99%
“…Several research works have paid attention to study the fissures in GBR kernel during fluidized bed drying. [8,9] The fissured GBR kernels tend to break and deform their shape during cooking, causing poor eating texture. A high number of fissured GBR during drying reduces the value of rice.…”
Section: Introductionmentioning
confidence: 99%
“…Drying operations as convective drying, hot-air oven, vacuum, osmotic, fluidized bed and superheated steam dehydration techniques are conventionally used to achieve water evaporation in shorter times. In GBR, drying procedure system and operation conditions affect the drying rate and quality attributes, whilst starch digestibility, GABA and dietary fiber content depend on the applied temperature (Chungcharoen et al, 2014;Srisang et al, 2011). These drying methods are still expensive and not always affordable in low and middle-income countries where rice production and transformation is performed with few economic resources.…”
Section: Introductionmentioning
confidence: 99%